PENGAARUH CURRENT RATIO ,NET PROFIT MARGIN DEBT ASSETS TO RATIO, DAN PERPUTARAN PERSEDIAAN TERHADAP LABA PERUSAHAN - Rizqiani Nur Rhomadhoni; Ismunawan, Ismunawan (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of further research is to obtain information about the effect of the power ratio, contribution margin, debt ratio and reserve turnover ratio on the company's bottom line. In his research, researchers used quantitative research methods to determine the samples according to the needs of the researchers. Six telecommunications coompanies are.listed on the Indonesia, Stock Exchange (IDX). which is used as a sample in conducting further research. The analysis tool is multiple regression, the result is that the current ratio (CR) has no. signiificant effect on company results, net profit margin has a positive but not significant effect, load ratio has a positive, and significant effect on company income. company results and sales. Company results are significant by company results